2005
DOI: 10.1007/s10747-005-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of chronic inflammatory processes and their treatment

Abstract: Proceeding from the known views of the functioning of the immune system, the main mechanism of its effector activity in fighting foreign material is development of an inflammatory process. The process also involves other systems or components, which results in the formation of a functional system intended for the most efficient elimination of the foreign agent. Thus, an inflammatory process is a normal defensive reaction of the body and, in a favorable case, reflects the normal work of the immune system. Two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has also been shown that inflammation can be a fundamental contributor to other degenerative conditions, such as diabetes, cancer and cardiovascular diseases. [5][6] Furthermore, the inflammatory response can be identified as the major cause of damage related to autoimmune diseases. 5 Consequently, the regulation of inflammatory processes is an essential avenue in the treatment of various pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that inflammation can be a fundamental contributor to other degenerative conditions, such as diabetes, cancer and cardiovascular diseases. [5][6] Furthermore, the inflammatory response can be identified as the major cause of damage related to autoimmune diseases. 5 Consequently, the regulation of inflammatory processes is an essential avenue in the treatment of various pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of immune and inflammatory processes, the iNOS expression clearly correlates with the disease progression that can point to its ototoxic and / or immunosuppressive effect [54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%